Analyzing Factors Influencing Students' and Teachers’ Pronunciation in Speaking English - Jihad, Suryani; Nasrun, Nasrun; Patawari, Arfah (Indonesian Journal Publisher, 2024)
This research aims to examine the factors that influence students' and teachers' creativity in speaking English. However, both non-native English students and teachers often face difficulties in this aspect. This research uses qualitative methods to identify factors that influence pronunciation in English for students and teachers. Data was collected through observation, interviews, and analysis. The findings of this research reveal that the influencing factors are the mother tongue, level of phonological awareness, practice habits, social interaction, and effective teaching methods. The influence of the mother tongue has proven to be an important factor in student and teacher pronunciation. Students whose native language has different sounds from English tend to have difficulty pronouncing these sounds accurately. The same applies to teachers with different mother tongues. The level of phonological awareness, which refers to the ability to distinguish and produce sounds in a language, also plays an important role in achieving good pronunciation. Students and teachers who actively engage in social interactions with native English speakers have a greater opportunity to improve their pronunciation skills. Lastly, effective teaching methods are important to improve student and teacher pronunciation.